2020
DOI: 10.3346/jkms.2020.35.e245
|View full text |Cite
|
Sign up to set email alerts
|

Acute Peripheral Facial Palsy: Recent Guidelines and a Systematic Review of the Literature

Abstract: Background This study reviews recent literature on facial palsy guidelines and provides systematic reviews on related topics of interest. Methods An electronic database search was performed to identify recent guidelines dealing with facial nerve palsy, systematic reviews and recent meta-analysis published between 2011 and 2019 (inclusive). The literature search used the search terms “Bell's palsy,” “Ramsay-Hunt syndrome,” “Facial palsy,” “Facial paralysis,” “Facial pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 43 publications
0
39
0
4
Order By: Relevance
“…In the children population, the most common causes of FNP are Bell’s palsy (60 to 80% of the cases) [ 9 , 11 , 12 ], infectious diseases, malignancies, trauma and congenital abnormalities [ 13 , 14 , 15 ]. Therefore, these are the causes to investigate in the history and physical examination.…”
Section: Causes Of Facial Nerve Palsymentioning
confidence: 99%
See 1 more Smart Citation
“…In the children population, the most common causes of FNP are Bell’s palsy (60 to 80% of the cases) [ 9 , 11 , 12 ], infectious diseases, malignancies, trauma and congenital abnormalities [ 13 , 14 , 15 ]. Therefore, these are the causes to investigate in the history and physical examination.…”
Section: Causes Of Facial Nerve Palsymentioning
confidence: 99%
“…Drack et al reported an idiopathic cause in 60.7% of children diagnosed with peripheral facial palsy (84 patients aged 10 months to 16 years) retrospectively between 1998 and 2007 in Switzerland [ 9 ]. The reactivation of herpes simplex virus-1 is presumed to support the pathogenesis of Bell’s palsy [ 5 , 13 ]. Symptoms are likely caused by facial nerve oedema, with the autoimmune system proposed to be involved in causing local myelin damage and an inflammatory process of the facial nerve, leading to its compression [ 11 , 16 , 17 ].…”
Section: Causes Of Facial Nerve Palsymentioning
confidence: 99%
“…Updated guidelines have confirmed steroids to be effective at increasing the possibility of complete facial functional recovery in acute FNP, while novel treatments such as nimodip-ine and mycophenolate mofetile are under study. Nonetheless, postoperative corticosteroid treatment for iatrogenic FNP is unadvised, although clear evidence is lacking [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of APFP is unclear; however, it is widely recognized as a result of reactivation of herpes simplex virus type 1 and varicella-zoster virus [ 3 ]. In addition to viruses, there are other potential causes, such as tumors, trauma, anatomical abnormalities, inflammation, ischemia, and acute cold exposure [ 4 , 5 ]. For APFP treatment, there is consensus that early use of prednisolone is effective; however, the use of antiviral drugs remains controversial.…”
Section: Introductionmentioning
confidence: 99%